A Study on Social Network Blogs as Political Tool on Information Technology Students' Perspective - Mohd Fadhli, Abdul Karim (2010)
The developments of newest communication technology, especially web based applications such as weblogs, have changed the media landscape. In countries with controlled media system, the emergence of weblogs provides an option medium to those who want to disseminate views generally suppressed by the mainstream media. Issues deemed sensitive by the local media seldom get due coverage. Even if there is coverage, it is presented from the viewpoint that is consistent with the views and philosophy of the elite and the government. Departing on the premise that blogging offers a relatively wider public sphere than the print media; discourses on political issues on different forms. Hence, this paper examines and discusses the perception, acceptance and belief of UUM IT student through political blog.